Photovoltaic Performance of ZnO Nanorod and ZnO : CdO Nanocomposite Layers in Dye-Sensitized Solar Cells (DSSCs). (10th October 2013) - Erten-Ela, Sule
Abstract : Triphenylene diamine sensitizer comprising donor, electron conducting, and anchoring group is synthesized for a potential application in dye-sensitized solar cells. Absorption spectrum, electrochemical and photovoltaic properties of triphenylene diamine have been investigated. Two different electrodes are used for dye-sensitized solar cells. The performances of ZnO nanorod electrodes are compared to ZnO : CdO nanocomposite electrode. Also, the theoretical calculations for HOMO and LUMO orbitals are used to estimate the photovoltaic properties of organic sensitizer in the design stage. ZnO : CdO nanocomposite electrode-based dye-sensitized solar cell sensitized with organic sensitizer exhibits higher efficiencies than ZnO nanorod electrode. For a typical device, a solar energy conversion efficiency (η ) of 0.80 based on ZnO : CdO nanocomposite is achieved under simulated AM 1.5 solar irradiation (100 mW cm −2 ) with a short circuit photocurrent density (J s c ) of 3.10 mA/cm 2, an open-circuit voltage (V o c ) of 480 mV, and a fill factor (FF) of 0.57. These results suggest that the ZnO : CdO nanocomposite system is a good selection and a promising candidate for electrode system in dye-sensitized solar cells.